Implementing Kurikulum Merdeka: Strengthening Scientific Literacy - Suci Perwita Sari; Edy Surya; Ismail Saleh Nasution3; Baihaqi Siddik Lubis; Mawar Sari (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2023)
The learning process has evolved from face-to-face to online, hybrid, and back to face-to-face. This change resulted in a number of changes, particularly in the learning curriculum, which began as the Kurikulum 2013, evolved into the Kurikulum Darurat, and is now being implemented as the Kurikulum Merdeka. The purpose of this research is to reinforce the importance of scientific literacy in the implementation of the Kurikulum Merdeka. The results of published research on the relationship of scientific literacy to Kurikulum Merdeka achievements are the subject of this study. The PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) method was used in this study. According to the findings, there is a relation between scientific literacy and the Kurikulum Merdeka. According to the findings of this study, students in the Kurikulum Merdeka for Elementary Schools are expected to cultivate environmental awareness and life skills. Meanwhile, scientific literacy necessitates an explanation of facts for all scientific phenomena. Thus, through scientific literacy, students are able to protect nature through scientific phenomena.